The Use of Population Attributable Risk to Estimate The Impact of Preventive Interventions of Smoking Cessation in Chronic Obstructive Pulmonary Disease(COPD) - Mahdieh Namayandeh (Journal of Community Health Research, 2020)
Chronic pulmonary disorders are a set of diseases that restrict respiration airflow(1).Most of these diseases are chronic obstructive pulmonary disease (COPD)(1). According to the WHO  report, mortality from COPD is increasing worldwide. It is expected to be the third leading cause of death worldwide by 2030(2) (the sixth leading cause of death in 1990(3). This disease causes significant costs for health systems(4). There is strong evidence between COPD and smoking as a major risk factor. Smoking cessation is the most effective measure to prevent or slow COPD progression (2,5). The effect of smoking on COPD was assessed in selected studies using the odds ratio (OR). The data analysis results using the random effects method showed that the risk of COPD was higher in smokers and those exposed to cigarette smoke.(current smoker; 95% CI: 0.78 – 4.31, OR: 1.83, Ex-smoker; CI: 1.05 - 4.98, OR: 2.29, passive smoker; CI: 0.43_3.08 , OR: 1.15)(3,6). According to the results of the 7th national survey of non-communicable disease risk factors (Steps 2016),the distribution of current smokers, ex-smokers, and passive smokers were 9.71, 14.63,and 31.53 among over 18 years old, respectively(7). Furthermore, the population attributed risk (PAR) of each factor with Levin formula (PAR=P(OR-1)/P(OR-1)+1) is 0.89%, 0.95%, and 82.5%, respectively, which indicates when smoking would eradicate in populations, we can propose to lower up to almost 90 % in the population’s  COPD.